HISTORY TEACHERS' UNDERSTANDING OF STUDENTS' LEARNING STYLES IN PUBLIC HIGH SCHOOL 2 GORONTALO - Rini, Sarini Laindjong; Manay, Helman; Hotimah, Iis Husnul (Satmata: Journal of Historical Education Studies, 2025)
The purpose of this study is to find out teachers' understanding of students' learning styles in history learning at SMA Negeri 2 Gorontalo. Teachers' understanding of students' learning styles is very important so that teachers know different student learning styles and to be able to adjust what kind of learning methods or models are suitable for students. SMA Negeri 2 Gorontalo is located in Gorontalo Province precisely on Jl. Rambutan, Buladu Village, West City, Gorontalo City, this school has a variety of student learning styles consisting of visual, auditory, and kinestic learning styles. method used in this study is a qualitative research method with data and descriptive analysis and interviews. The results of the study show that the understanding of history teachers of students' learning styles is very clear that history teachers in SMA Negeri 2 Gorontalo understand students' learning styles. Learning style is one of the most important parts of the teaching and learning process. The results showed that teachers' understanding of students' learning styles that every history teacher at SMA Negeri 2 Gorontalo understands students' learning styles and tries to adjust to learning methods such as discussions, lectures and the use of learning media by showing historical documentary videos.